Androgen-induced masculinization in rainbow trout results in a marked dysregulation of early gonadal gene expression profiles - Houlgatte Rémi; Montfort Jérôme; Baron Daniel; Fostier Alexis; Guiguen Yann (BMC Genomics, 2007)
Abstract Background Fish gonadal sex differentiation is affected by sex steroids treatments providing an efficient strategy to control the sexual phenotype of fish for aquaculture purposes. However, the biological effects of such treatments are poorly understood. The aim of this study was to identify the main effects of an androgen masculinizing treatment (11β-hydroxyandrostenedione, 11βOHΔ4, 10 mg/kg of food for 3 months) on gonadal gene expression profiles of an all-female genetic population of trout. To characterize the most important molecular features of this process, we used a large scale gene expression profiling approach using rainbow trout DNA microarrays combined with a detailed gene ontology (GO) analysis. Results 2,474 genes were characterized as up-regulated or down-regulated in trout female gonads masculinized by androgen in comparison with control male or female gonads from untreated all-male and all-female genetic populations. These genes were classified in 13 k-means clusters of temporally correlated expression profiles. Gene ontology (GO) data mining revealed that androgen treatment triggers a marked down-regulation of genes potentially involved in early oogenesis processes (GO 'mitotic cell cycle', 'nucleolus'), an up-regulation of the translation machinery (GO 'ribosome') along with a down-regulation of proteolysis (GO 'proteolysis', 'peptidase' and 'metallopeptidase activity'). Genes considered as muscle fibres markers (GO 'muscle contraction') and genes annotated as structural constituents of the extracellular matrix (GO 'extracellular matrix') or related to meiosis (GO 'chromosome' and 'meiosis') were found significantly enriched in the two clusters of genes specifically up-regulated in androgen-treated female gonads. GO annotations 'Sex differentiation' and 'steroid biosynthesis' were enriched in a cluster of genes with high expression levels only in control males. Interestingly none of these genes were stimulated by the masculinizing androgen treatment. Conclusion This study provides evidence that androgen masculinization results in a marked dysregulation of early gene expression profiles when compared to natural testicular or ovarian differentiation. Based on these results we suggest that, in our experimental conditions, androgen masculinization proceeds mainly through an early inhibition of female development.